Facilitating Personal Transformation for Sustainability: A Learning Program on the Sustainable Development Goals, Combining a Card Game and a Self-Reflective Questionnaire - Kitamura, Kenji; Ito, Koji (Frontiers in Sustainability, 2022)
Sustainable Development Goals (SDGs) require transformations at all levels, from global to local, to be realized. Underlying all of these levels is the personal level, where any transformation begins. Before individual persons change their behavior for sustainability, they will need to not only understand the SDGs, but also regard them as a matter which directly concerns them. A process involving “personalizing the SDGs” needs to exist between initial awareness and subsequent action. However, identifying and instituting the means by which this can be realized is not easy. In this study, we designed a learning program that combined an existing SDGs game with an original self-reflective questionnaire, and implemented it in Ishikawa Prefecture, Japan. The program allowed participants (n=289) to first play the game, which takes the form of a simulation of the world in the run up to 2030, and then carry out individual and/or group work to consider their individual, specific relationships with the global agenda. The questionnaire also provided each participant with a means to reflect on their initial perceptions and how they changed following this learning. The answers on the questionnaire indicated that the program aided the participants in raising their perceived levels of relationships with, and the personal significance of, the SDGs, while having fun at the same time. Personal relationships with the SDGs were expressed more concretely when local contexts and topics covered in other learning programs were tied in with the SDGs.